Invasive Meningococcal Disease due to group C N. meningitidis ST11 (cc11): The Tuscany cluster 2015–2016. Issue 40 (25th September 2018) - Menichetti, Francesco; Fortunato, Simona; Ricci, Andrea; Salani, Francesca; Ripoli, Andrea; Tascini, Carlo; Fusco, Francesco Maria; Mencarini, Jessica; Bartoloni, Alessandro; Di Pietro, Massimo
Abstract: Objectives: To describe the cluster of MenC ST11 Invasive Meningococcal Disease (IMD) occurred in Tuscany in the years 2015–2016. Methods: A retrospective charts analysis of clinical, epidemiological and microbiological aspects of documented IMD was performed. Prognostic factors for death were evaluated. Results: Sixty-one patients with IMD in the 2015–2016 period were documented: 28 had meningococcemia, 24 meningitis plus meningococcemia and 9 meningitis. MenC ST11 (cc11) was identified in 48/54 (89%) of the tested strains. All patients, with the exception of three very early death, received timely and appropriate antibiotic therapy and, in selected case, adjunctive therapy with steroids and Pentaglobin®. Forty-one patients recovered (67.3%, mean age: 26 years), 7 had permanent sequelae (11.3%, mean age 31 years) and 13 died (21.3%; mean age: 46 years). In a multivariate analysis, septic shock, purpura fulminan s and advanced age were negative prognostic factors, while emergency admittance to a tertiary-care, university hospital, positively influenced the survival rate. The epidemiological analysis of the cluster identified close contacts and recreational environments such as discos as hotspot for MenC transmission. After a massive vaccination campaign, the number of MenC cases reported in Tuscany in 2017 decreased to 10, with no death. Conclusions: Vaccination campaign of key populations together with the need for rapid and qualified emergency care of the affected patients seems to be the main lesson learned by the MenC ST11 Tuscany epidemic.